2005
DOI: 10.1136/vr.157.12.341
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic parameters of normal alpacas (Lama pacos)

Abstract: The electrocardiographic parameters of 40 healthy alpacas (Lama pacos) were recorded with a base-apex lead system to establish the normal resting electrocardiographic parameters in this species. The following parameters were measured: heart rate and rhythm, QRS and T morphology, ST segment position, P amplitude and duration, QRS duration and PQ and QT intervals. The heart rate varied between 50 and 110 bpm, with a mean (sd) of 80 (17.8) bpm, and no significant differences were observed between males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
3
0
5
Order By: Relevance
“…Recently, anesthesia in camel has gained an interest in veterinary clinic because, it represent solve of camel problems, surgical treatment and provide a good line of treatment of many problems in camels. The results of electrocardiogram (ECG) reported a negative T weave in 4 of 5 camel in group I as depicted in figure (1) in lead I, II and III , this data was in consistent with the previous results of Fresh etal., 27 in their study in Illama; they found that T weave was commonly -ve in healthy normal camelida. Furthermore, ketamine and medetomidine injection in camel as anesthetic and sedation drugs can changes the electrical activity in the cardiac muscle (heart) in one humped camel.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, anesthesia in camel has gained an interest in veterinary clinic because, it represent solve of camel problems, surgical treatment and provide a good line of treatment of many problems in camels. The results of electrocardiogram (ECG) reported a negative T weave in 4 of 5 camel in group I as depicted in figure (1) in lead I, II and III , this data was in consistent with the previous results of Fresh etal., 27 in their study in Illama; they found that T weave was commonly -ve in healthy normal camelida. Furthermore, ketamine and medetomidine injection in camel as anesthetic and sedation drugs can changes the electrical activity in the cardiac muscle (heart) in one humped camel.…”
Section: Discussionmentioning
confidence: 94%
“…Some animals are not readily available for study such as rhinoceros [24] and grizzly bears [25] because of the difficulty in capturing them for study. Domesticated animals have been studied in larger numbers and include cows (N = 1247) [26][27][28], donkeys (N = 240) [29,30], goats (N = 344) [28,31], camels (N = 146) [32,33], llamas and alpacas (N = 156) [34][35][36] and cats [37][38][39]. Various kinds of horses (N = 918) have had an ECG including Andalusian, thoroughbreds and standard horses [40,41] as well as ponies [42].…”
Section: Resultsmentioning
confidence: 99%
“…En nuestro estudio los animales no fueron anestesiado, además de usarse dos posiciones para la ECG estación y decúbito lateral derecho, comunemente usada en animales jovenes (menores de 6 meses de edad). Asimismo, la electrocardiografía nos permitió la evaluación del ritmo cardiáco y patrones de conducción eléctrica, tecnica usada para describir algunos valores referenciales en estudios en alpacas y llamas (Ferasin et al, 2005;Krause et al, 2004).…”
Section: Discussionunclassified
“…Hemos podido determinar que la frecuencia en neonatos es de 124,83 en estación y en decúbito de 114,16. Según Ferasin et al, 2005 la frecuencia cardiaca en alpacas adultas y saludables tiene un rango entre 50 y 110 latidos/minuto con una media de 80, con lo cual observamos que los valores en las crías de alpaca son más elevados. En otros camelidos como las llamas sucede un fenómeno similar, pues los adultos tienen un frecuencia de 80 y las crías de 120 (Hoffman, 2006), por otra parte en animales filogéticamente cercanos a los camélidos sudamericanos como los camellos dromedarios jovenes la frecuencia cardiaca tuvo un valor promedio de 60 latidos por minuto (Lapiccirella y Abboni, 1961); mientras que en terneros holstein de 27-31 días de edad el valor promedio fue de 112 latidos por minuto (Mendes et al, 2001).…”
Section: Discussionunclassified